Removal of Crystal Violet Dye in Aqueous Solution by Adsorption onto Adsorbents Derived from Peanut Shells - Yasarawan, Nuttawisit (Burapha Science Journal, 2026)
Batch experiments were carried out to study the adsorption of crystal violet onto the adsorbents derived from acid-treated peanut shells (APS) and untreated peanut shells (UPS), at the initial dye concentrations of 10.7 – 15.4 mM and the temperatures of 27 – 47 oC, with the adsorbent dosage being kept at 1.2 g L-1. Under all conditions attempted, the adsorption equilibrium was achieved within 35 minutes of the contact time. Acid treatment significantly promoted the dye removal efficiency of the adsorbent. The maximum dye removal percentages were 96.37% and 99.96% for UPS and APS, respectively. All kinetic data for the adsorption fit well to the pseudo-second-order equation. The activation energies for the adsorption onto UPS and APS were 21.04 and 25.35 kJ mol-1, respectively. The relationship between the adsorption quantity and the dye concentration at equilibrium followed the Langmuir isotherm for the monolayer adsorption. According to the thermodynamic analysis based on the van 't Hoff equation, the enthalpies of adsorption onto UPS and APS were 14.8 kJ mol-1 (endothermic type) and -22.4 kJ mol-1 (exothermic type), respectively. As the Gibbs energies of adsorption were all negative, the adsorption process could spontaneously take place when the dye solution was in contact with the adsorbent.